Atypical acute disseminated encephalomyelitis with systemic inflammation after a first dose of AztraZaneca COVID-19 vaccine. A case report - Bastide, Laure; Perrotta, Gaetano; Lolli, Valentina; Mathey, Céline; Vierasu, Ortensa-Irina; Goldman, Serge; Vandergheynst, Frédéric (Frontiers in Neurology, 2022)
Background: Only a few cases of acute disseminated encephalomyelitis (ADEM) following coronavirus disease 19 (COVID-19) vaccination have been described since the beginning of the vaccination campaign. Results: Here we report the first case of central nervous system (CNS) demyelination with systemic inflammatory findings on whole body 19-fluorodeoxyglucose positron emission tomography with computed tomography (FDG-PET/CT) following the ChAdOx1 nCoV-19 vaccine. Conclusions: Clinicians should stay aware of potential new adverse events after immunization.